Auto production in South Africa and components manufacturing in Gauteng Province - Alex Mohubetswane Mashilo (International Labour Organization (ILO), 2019)
This paper presents an exposition of the state, contribution and performance of automotive Global Value Chains in South Africa with a focus on manufacturing. The research process followed was greatly supported by years of working experience in the industry. A survey was conducted to look at the state of social upgrading. This was followed by in-depth interviews focusing on firm-level economic upgrading. Extensive document analysis was conducted. Despite being an important part of the process, economic upgrading does not always produce social upgrading. Component manufacturing enterprises are sandwiched between downward market pressures exerted by original equipment manufacturers on the one hand and their employees who are pushing social upgrading improvements on the other. Their conditions are inferior compared to those of their counterparts in the vehicle assembly sector. A lacklustre economic upgrading response by their employers to market pressures produces loss of volume or supply contracts, or a failure to secure new original equipment components and supplier parts manufacturing contracts, among other possible consequences. This generates social downgrading for the workers first and foremost in the form of retrenchments. The creation of new jobs and sustenance of existing employment levels require increases in production volumes, supported by deepening and widening value addition, due to intensifying process upgrading involving automation and robotisation coupled with new and more efficient methods of work and production systems.
Keywords: 330